PLACE DE LA DÉMARCHE D’INVESTIGATION DANS L’ENSEIGNEMENT DES SCIENCES DE LA VIE ET DE LA TERRE AUX COLLÈGES - Hassouni, Taoufik; Ameziane, Nour-eddine; Houssaini, Wissal Iraqi; Lamri, Driss; El Madhi, Youssef; Haiba, Rachid Ben (European Scientific Journal, ESJ, 2014)
In the teaching of Life Sciences and Earth, the inquiry approach has regularly reaffirmed importance, particularly with regard to the science. Its implementation requires the social constructivist perspective of its references. The present study helps, in a first time to analyze the conceptions of teachers and learners about the process of investigation and teaching paradigms. In a second step we have sought to analyze the content of textbooks dealing with teaching materials related to this new approach, detailed results are presented and discussed.